Relationship between peer victimization and depressive symptoms among secondary vocational health school students： the chain mediating role of positive mental health and social media addiction - Li Houyi; Xu Chun; Hu Shasha; Xiang Bo; Liu Kezhi (Sichuan jingshen weisheng)
BackgroundStudents in secondary vocational health school are at the age of puberty and prone to depressive symptoms. Peer victimization and social media addiction are found to be crucial in influencing the development of depression， and positive mental health has been proven to alleviate depressive symptoms， whereas there remains a striking lack of research on the mediating role of positive mental health and social media addiction in the relationship between peer victimization and depressive symptoms among secondary vocational health school students.ObjectiveTo explore the relationship between peer victimization and depressive symptoms and investigate the mediating role of positive mental health and social media addiction， so as to provide references for the prevention of depression among secondary vocational health school students.MethodsFrom October to December 2020， a cluster sampling framework was utilized to recruit 7 307 students from a secondary vocational health school in Luzhou City， Sichuan Province. Assessments were performed using Multidimensional Peer Victimization Scale （MPVS）， Warwick-Edinburgh Mental Well-being Scale （WEMWBS）， Bergen Social Media Addiction Scale （BSMAS） and Patient Health Questionnaire Depression Scale-9 item （PHQ-9）. Spearman correlation analysis was calculated to determine correlations between scores of scales， Process 4.0 was employed to test the mediation effect， and the bias-corrected Bootstrap procedure was used to test the significance of the mediation effect.ResultsA total of 7 044 （96.40%） valid questionnaires were collected. And 4 391（62.34%）students were found to have depressive symptoms. Correlation analysis revealed that PHQ-9 score was positively correlated with BSMAS score and MPVS score （r=0.404， 0.506， P<0.01）. WEMWBS score was negatively correlated with PHQ-9 score， BSMAS score and MPVS score （r=-0.587， -0.259， -0.358， P<0.01）. BSMAS score was positively correlated with MPVS score （r=0.328， P<0.01）. Positive mental health played a mediating role in the relationship between peer victimization and depressive symptoms， with an indirect effect value of 0.130 （95% CI： 0.119~0.141）， accounting for 30.81% of the total effect. Social media addiction also mediated the relationship between peer victimization and depressive symptoms， with an indirect effect value of 0.052 （95% CI： 0.045~0.059）， accounting for 12.34% of the total effect. Positive mental health and social media addiction exhibited a chained mediation effect on the relationship between peer victimization and depressive symptoms， with an indirect effect value of 0.012 （95% CI： 0.010~0.014） and accounting for 2.84% of the total effect.ConclusionPeer victimization can affect the presence of depressive symptoms among secondary vocational health school students both directly and indirectly through either separate or chained mediation of positive mental health and social media addiction.